New protocol for diagnosing exercise-induced arrhythmias and conduction disturbances in early and preschool age children - E. S. Vasichkina; D. Yu. Alekseeva; E. Yu. Gorozhankina; A. S. Kresteleva; O. A. Kofeynikova; T. M. Pervunina (Российский кардиологический журнал, 2022)
Aim. To develop a protocol for diagnosing exercise-induced arrhythmias and conduction disturbances in children aged 3-6 years without structural heart disease.Material and methods. The study included 20 patients (11 boys) aged 58,7±2,12 months with ventricular arrhythmias (VA) and/or atrioventricular (AV) block according to single electrocardiographic (ECG) records and/or 24-hour ECG monitoring. All patients underwent a thorough clinical and paraclinical examination, including exercise stress testing using original and Bruce protocols. The termination criteria were the first of following events: achievement of the heart rate set by the study aim; the appearance and/or aggravation of potentially dangerous arrhythmias and conduction disorders (single premature ventricular contraction (PVCs) with increasing frequency, and/or early PVCs, and/or paired PVCs, and/ or ventricular tachycardia (VT), and/or AV block); registration of allorhythmia (bigeminy) within 10 seconds.Results. The termination criteria using the original protocol were achieved in all patients (n=20, 100%) compared to the standard Bruce protocol (n=5, 25,0%), p<0,001. The number of steps passed was significantly higher using original protocol (5,0 [5,00-6,00]) than when using the standard protocol Bruce 2,0 [2,03,0], p<0,05. Exercise tolerance was significantly higher when using the original protocol than the standard Bruce protocol (p<0,05). The probability of reaching the termination criteria using the original protocol were 116 times greater than using the standard Bruce protocol (odds ratio, 116, 95% confidence interval: 5,932250, p=0,0017). VAs were registered in 20,0% (n=4) of patients using the original protocol, while AV blocks — in 20,0% (n=4). Among the five patients who achieved the termination criteria using the standard Bruce protocol, VAs were recorded in 10,0% (n=2) of patients, while AV blocks — in 5,00% (n=1).Conclusion. The use of exercise test with an original protocol makes it possible to achieve the termination criteria, increases its information content and diagnostic significance. It makes it possible to determine the nature of VAs and AV conduction dosorders.